DEVELOPMENT OF INNOVATION EDUCATION THROUGH BLENDED LEARNING - Prasetyo, Teguh; Widyasari, Widyasari; Hartono, Rudi (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2016)
Development courses Educational Innovation is based on the analysis of the needs that exist in FKIP Djuanda Bogor University for a study to be carried out face-to-face and through/within network (Online). This can affect the mindset lecturers to continue to maximize learning to be more effective and efficient so that students can absorb the knowledge, skills, and attitudes. The purpose of this research is to design and develop an open course materials Innovation blended learning based education that is appropriate to the achievement of graduation Prodi PGSD on the first semester 2016/2017. This study refers to the development of which was developed by the Directorate of Education and Student Affairs consisting of (1) the analysis phase, (2) the design stage, and (3) the development stage. This research was developed and implemented for four months from June to September 2016 in Prodi PGSD FKIP University Djuanda Bogor. The results of the study material Outdoor Education Innovation begins with analyzing the needs of the development phase, design phase material content of Educational Innovation, and the stage of development which include team development process pengampu courses and a small scale trial with five PGSD semester students. The conclusion of the development of open innovation educational materials as follows; (1) Development of courses open Educational Innovation has been developed according to the concept of achievement of graduation courses, (2) Subject of Educational Innovation developed blended learning easier for students PGSD Semester 5 FKIP University DJuanda Bogor to obtain course materials offline, (3 ) students of the fifth semester PGSD give a positive response will be the development of an open matter Education Innovation.